ANTIFUNGAL ACTIVITY OF SEAWEED ULVA LACTUCA L. EXTRACTED CRUDE PROTEIN AGAINST PATHOGENIC FUNGI - R, KRISHNAMOORTHI; SR, SIVAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate the antifungal activity of seaweed extracted protein against the pathogenic fungi. Methods: Antifungal activity of seaweed Ulva lactuca L. extracted protein was determined against pathogenic fungi such as Alternaria solani, Aspergillus clavatus, Aspergillus niger, Aspergillus flavus, and Fusarium oxysporum by disk diffusion Method. Then, the potentially active protein was determined using sodium dodecyl sulfate-polyacrylamide gel electrophoresis and circular dichroism (CD) spectroscopy. Results: Seaweeds extracted protein checked for the antifungal activity against A. clavatus, A. solani, and A. flavus better activity compared to standard amphotericin-B and CD spectroscopy. Analysis of the extracts divulges the presence of entire protein compounds. Conclusions: This study extracted seaweed protein sufficient of antifungal activity opposed to antifungal pathogens as compared with the standard. This is first report an activity of seaweed extracted protein against the plant and human pathogenic fungus bearing agricultural important.